Nasionalisme dan Persoalan Identiti Politik di Sempadan: Kajian Kes Komuniti Murut Bantul, Daerah Nabawan, Sabah - Othman, Zaini (ASPENSI in Bandung, Indonesia, 2008)
ABSTRACT: In todayâs age of information, the issue of national identity and a nationâs security seems to be at stake and frequently challenged in various manners. The process of globalization has generated massive degree of openness that straddles national boundaries and thus takes its toll on national identity and security. Contemporary scholars such as Robertson (1992), Giddens (1990) and Ohmae (1995) reiterate that the phenomenon of globalization has brought up some kind of community with diverse socio-cultural backgrounds. As the world is becoming integrated, nationalism is said to be on the decline. To dwell on this argument, this article seeks to analyze the feeling of nationalism among the community in border areas of Sabah (Malaysia) and Kalimantan Timur (Indonesia). Focusing on the Murut community in a village called Bantul in Nabawan, Sabah, the writer undertakes to assess the communityâs sense of values, norms and political self-identity with respect to nationalism in Malaysia. In doing so, this study was done by focusing and examining the historical socio-political stage of ethnic identity formation in Sabah through casual effect factors from its early stages until to date. This study concludes that ethnic identity at the border, if not carefully guarded would likely emerge as a political threat to the national stability.Key words: nationalism, ethnic identity, globalization, border culture and social integration in Sabah, Malaysia.About the Author: Zaini Othman, M.A. ialah Pensyarah Hubungan Antarabangsa di Sekolah Sains Sosial UMS (Universiti Malaysia Sabah). Beliau dilahirkan di Pasir Mas, Kelantan pada 27hb April 1967. Memperolehi ijazah pertama dalam bidang Sains Politik dari UKM (Universiti Kebangsaan Malaysia) Bangi, pada tahun 1991; dan ijazah Sarjana (M.A.) dari University of Manchester, United Kingdom (1993-1995) dalam jurusan Pembangunan Politik & Ekonomi Politik Antarabangsa. Antara hasil penulisan beliau ialah Kenegaraan Malaysia (Kuala Lumpur: Fajar Bakti, 2005); Demokrasi, Kepimpinan & Keselamatan dalam Politik Malaysia (Bangi: Penerbit UKM, 2006); âBarisan Nasional dan Persoalan Hegemoni Politikâ dalam Jebat: Jurnal Jabatan Sejarah (Bangi: FSSK-UKM, 2003); dan âElections in Democratic Hegemonic Stateâ dalam JATI: Jurnal Ilmu Sosial (Kuala Lumpur: Universiti Malaya, 2007). Beliau juga telah membentang dan menyertai pelbagai seminar, samada di peringkat domestik ataupun antarabangsa. Bersabit kepentingan akademik, beliau boleh dihubungi dengan alamat e-mail: zo@ums.edu.my atau znothman@yahoo.comHow to cite this article? Othman, Zaini. (2008). âNasionalisme dan Persoalan Identiti Politik di Sempadan: Kajian Kes Komuniti Murut Bantul, Daerah Nabawan, Sabahâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.1 [Mei]. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112, pp.141-166.Chronicle of the article: Accepted (January 10, 2008); Revised (April 10, 2008); and Published (May 20, 2008).